An epigrammatic status of the 'azole'-based antimalarial drugs. Issue 2 (23rd December 2019) - Sharma, Mousmee; Prasher, Parteek
Abstract : The review presents an epigrammatic collation of the contemporary antimalarial therapeutics based on various 'azole'-based motifs for targeting both the drug-resistant and drug-susceptible Plasmodium parasite. Abstract : The development of multidrug resistance in the malarial parasite has sabotaged majority of the eradication efforts by restraining the inhibition profile of first line as well as second line antimalarial drugs, thus necessitating the development of novel pharmaceutics constructed on appropriate scaffolds with superior potency against the drug-resistant and drug-susceptible Plasmodium parasite. Over the past decades, the infectious malarial parasite has developed resistance against most of the contemporary therapeutics, thus necessitating the rational development of novel approaches principally focused on MDR malaria. This review presents an epigrammatic collation of the epidemiology and the contemporary antimalarial therapeutics based on the ' azole ' motif.